Caco-2 Invasion by Cronobacter sakazakii and Salmonella enterica Exposed to Drying and Heat Treatments in Dried State in Milk Powder - Lang, Emilie; Guyot, Stéphane; Alvarez-Martin, Pablo; Perrier-Cornet, Jean-Marie; Gervais, Patrick (Frontiers in Microbiology, 2017)
Due to the ability of foodborne pathogens to survive in low moisture food, the decontamination of milk powder is an important issue in food protection. The safety of food products is, however, not always insured and the different steps in the processing of food involve physiological and metabolic changes in bacteria. Among these changes, virulence properties may also be affected. In this study, the effect of drying and successive thermal treatments on the invasion capacity of Salmonella Typhimurium, Salmonella Senftenberg, and Cronobacter sakazakii was assessed. Bacteria were dried on milk powder at three different water activity levels (0.25, 0.58 and 0.80) and heated at two different temperatures (90°C and 100°C) for 30 s and 120 s. After recovery, stressed bacterial populations were placed in contact with Caco-2 cells to estimate their invasion capacity. Our results show that drying increases the invasion capacity of foodborne pathogens, but that heat treatment in the dried state did not exert a selective pressure on bacterial cells depending on their invasion capacity after drying. Taken together, our findings add to the sum of knowledge on food safety in dried food products and provide insight into the effects of food processing.